Flexible Microcredit: Effects on Loan Repayment and Social Pressure - Kristina Czura; Anett John; Lisa Spantig (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Flexible repayment schedules allow borrowers to invest in profitable yet risky projects, but practitioners fear they erode repayment morale. We study repayment choices in rigid and flexible loan contracts that allow discretion in repayment timing. To separate strategic repayment choices from repayment capacity given income shocks, we conduct a lab-in-the-field experiment with microcredit borrowers in the Philippines. Our design allows us to observe social pressure, which is considered both central to group lending, and excessive in practice. In our rigid benchmark contract, repayment is much higher than predicted under simple payoff maximization. Flexibility reduces high social pressure, but comes at the cost of reduced loan repayment. We present theoretical and empirical evidence consistent with a strong social norm for repayment, which is weakened by the introduction of flexibility. Our results imply that cooperative behavior determined by social norms may erode if the applicability of these norms is not straightforward.
Keywords: O16; D90; G21; 330; peer punishment; social norms; microfinance; flexible repayment